Quality assessment of biogas and biol from two cow manure mixtures in PVC tubular biodigesters - Quipuzco Ushñahua, Lawrence (2011)
In this study, it was evaluated the quality of biogas and biolwhich are produced in tubular bio-digesters of PVC with two different mixtures: one with a ratio of 1/4 between manure and water, and other with a ratio of 1/5. These biodigesters were installed for researching in the Model Center of Waste Treatment – CEMTRAR of Universidad NacionalAgraria La Molina. The monitoring and analysis of biogas and biol were conducted from November 2009 to April 2010. It reached an average of 52% of CH4and 37.4% of CO2in the mixture of ¼, and an average of 53% of CH4 y 36.9% de CO2in the mixture of 1/5. The obtained biol in the study has a good amount of N-P-K. The quantities of Ca, Mg and Na found in the mixtures are similar to the organic fertilizers; therefore they can be used as fertilizers in hydroponic crops. The biol in fecal coliforms reached an average of 6.08x103 NMP/100 ml y 1.27x103 NMP/100 ml in mixtures of1/4 y 1/5 respectively, exceeding the maximum limits for the mentioned irrigation by the World Health Organization. With reference to the parasites: protozoa and helminthes, the average value of the mixtures of 1/4 and 1/5 wasof 0 org/lfor both mixtures. The results of this investigation will be very useful for the development of larger projects in order to reuse the cow’s waste from the dairy farm of the UNALM.